Paulella, new name for a Bryozoan Homonym (Cyclostomata) - Gontar, Valentina I. (Zootaxa, 2009)
The recent unintentional creation of a bryozoan secondary homonym requires a change of name for the species affected. Gontar (2009) established the new monotypic genus Paulina (order Cyclostomata), with type species Paulina taylori, for a small, ramifying uniserial species of Oncousoeciidae from the upper shelf of the Pacific coast of the middle Kurile Islands, Russia. Paulina Gontar, 2009 is preoccupied by Paulina Grigelis, 1977 (Protozoa, Foraminifera). Paulella nom. nov. (gender feminine) is here proposed as a replacement genus, resulting in the new combination Paulella taylori (Gontar, 2009).